The use of targets to improve the precision of mobile laser scanning - Abdulrahman, Farsat Heeto (2013)
A Mobile Laser Scanning System (MLSS) is a kinematic platform combining different sensors, namely: GPS, IMU and laser scanner. These sensors are integrated and synchronised to a common time base providing 3D geo-referenced data. MLSS is used in several areas; such as 3D urban and landscape modelling for visualisation in planning and road design, simulations for environmental management, and to support land use decision-making.